Chief Complaints of Patients Seeking Periodontal Treatment: An Institutional Study - Bista, Soni; Ranjit, Rebicca; Subedi, Suraksha (Journal of Institute of Medicine Nepal, 2022)
Introduction: The patient’s chief complaint is considered a vital component during diagnosis and treatment planning, but it is usually influenced by the severity of the disease. The aim of this study was to identify the most common chief complaints among patients visiting a Tertiary Care Center. Methods: This is a descriptive cross sectional study, carried out from September, 2020 to March, 2021 at Gandaki Medical College Teaching Hospital. Ethical approval was taken from Institutional Review Committee (Reference Number:96/77/78). Convenient sampling was done. The relevant presenting chief complaints were recorded and a rank order was created based upon their frequency. The data were entered into the excel sheet and the frequency distribution of the parameters were analyzed. Results: Among 420 patients, the most common chief complaint was deposits/stains, which was found to be 136 (32.38%) (0.27-0.37 at 95% confidence interval). The second most common complaint was bleeding gums, which was found to be 45 (10.71%), and the third was loose teeth 43 (10.24%), followed by pain 42 (10%), and gum swelling 33 (7.86%). The least common complaints reported were oral ulcer, tooth replacement, etc. Conclusion: The most common chief complaint was deposit/stains which was lower in our study when compared to other studies done in similar settings.